Women in protestantism - the image of baroness Elizabeth Kalisz (Slavic Studies, 2024)
This article is a linguistic and cultural analysis of the text of a memorial sermon from 1772 dedicated to Elisabeth Kalisz. This person was a baroness, a Prostestant, and lived in Drogomysl (Śląsk Cieszyński). The text of the sermon shows that the highest valued qualities of Protestant women were exemplary married life, motherhood and piety. The Cieszyn Protestants paid special attention to the education of women.
Keywords: sermon; Protestantism; Śląsk Cieszyński; Elżbieta Kalisz